Implementasi Teknologi Geofencing Untuk Pengawasan terhadap Lansia Menggunakan Sarung Lengan Berbasis Mikrokontroler dan Android - Amadea Permana; aad hariyadi; nanak zakaria (Jurnal Jaringan Telekomunikasi, 2020)
According to the World Health Organization (WHO), an elderly person is someone who has entered the age of 60 years and over. Based on recorded data from Radio Suara Surabaya from January 2017 to July 2019, Radio Suara Surabaya has received 618 listener reports of missing people due to dementia or senility. This research aims to provide an alternative in order to keep an eye on the presence of the elderly by utilizing the U-Blox Neo 6m GPS module and the ESP8266 NodeMCU microcontroller. In addition, supervisors can use an android application to implement geofence technology. The results of the research conducted gave the results by testing the GPS U-Blox Neo 6m module placed in different locations and conditions resulting in receiving information signals obtained from 3-9 information satellites that send signals. The distance difference test was carried out at 10 different location points resulting in a difference in the distance from 1 m to 8 m. In addition, there is data transmission delay testing carried out at different times of the morning, afternoon, and night which results in delays ranging from 0.2 seconds to 1 second. Based on the research conducted, it can be concluded that the implementation of geofence results in a geofence application that can apply geofence to the elderly by depicting a circle radius of 100 m based on the center point of a specified location. The use of GPS U-Blox Neo 6m gives results by calculating the average distance difference of 3.7m.